Metabolismo secundário dos fungos Penicillium sp e Fusarium moniliforme isolados como endofíticos de Melia azedarach (Meliaceae) - Santos, Regina Maria Geris dos (2003)
From healthy tissues of M. azedarach, 59 isolates of endophytic fungi were obtained, representing eight genera (one Ascomycetes, one Basidiomycetes and six Hyphomycetes). Genera Aspergillus and Penicillium were the most found in this present study. Extracts of two fungal strains, Penicillium sp e Fusarium moniliforme were investigated chemically. This investigation resulted in the isolation of 34 pure compounds. Three were obtained from F. moniliforme: two depsidipeptides (bassiatin and a new natural product) and the ergosterol peroxide. From the Penicillium sp were isolated 10 novel meroterpenes (preaustinoid A, preaustinoid B, preaustinoid A2, preaustinoid A1, austinolide, preaustinoid B1, isoaustinone, austinoneol, preaustinoid B2, and preaustinoid A3), three known meroterpenes(acetoxydehydroaustin, dehydroaustin, and neoaustin). The other two meroterpenes are still to be identified. In addition, it has been found five lignans compounds (two were identified as novel natural products), six alkaloids (three of them identified as verruculogen, Tr-2 and its isomer), two lactones derivatives (penicillic acid and dehidropenicillic acid), one nucleoside (uridine) and two poliols (eritritol and mannitol). Some extracts and fractions from these two microorganisms were submitted to biological assays (antibacterial and insecticidal). The meroterpene dehydroaustin showed a great insecticidal activity against the mosquito Aedes aegyptii. An analytical strategy, based on liquid-chromatography-mass spectrometry hyphenation was established for the comparison of the secondary metabolites composition of the host plant and the fungus Penicillium sp. This methodology had the meroterpenes and limonoids from M. azedarach as targets in order to compare the metabolism between these two associated organisms. Liquid chromatography-mass spectrometry methodology allowed the standard meroterpenes identification in the extracts derived from this microorganism cultivated on rice and maize, as well as, other metabolites, verruculogen, uridine and a new lignan. Gas chromatography-mass spectrometry analysis supplied the apolar constituents identification of the fungus on distinct substrates. Biogenetics studies involving molecular biology related to meroterpenes were carried out using the tetraketide precursor 3,5 dimethyl orsellinic acid. As a result of this, were found three related genes to polyketides (non-reduced, partially reduced, and highly modified) and C-methyltransferase gene. It suggests a relationship between these genes and the meroterpenoid production. Further studies should be carried out in order to investigate this relation.